Non-Invasive Brain Stimulation and Artificial Intelligence in Communication Neuroprosthetics: A Bidirectional Approach for Speech and Hearing Impairments - Rudroff, Thorsten (MDPI, 2025)
This perspective paper introduces a novel bidirectional framework for communication neuroprosthetics that integrates non-invasive brain stimulation (NIBS) with artificial intelligence (AI) to address both speech production and auditory processing impairments. Traditional approaches typically target only one aspect of communication, while this framework supports the complete communication cycle. The integration of transcranial direct current stimulation (tDCS) and transcranial alternating current stimulation (tACS) with advanced AI algorithms enables the personalized, adaptive enhancement of neural signals for both speaking and listening functions. This paper examines current evidence for NIBS efficacy in communication disorders, explores AI innovations in neural signal processing, and discusses implementation considerations for closed-loop systems. This bidirectional approach has the potential to provide more natural, effective communication support while promoting neuroplasticity for long-term recovery. The framework presented offers a roadmap for developing accessible communication interventions that could significantly improve the quality of life for individuals with speech and hearing impairments resulting from neurological conditions.